2022
DOI: 10.3390/molecules27185825
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Ultrasound in Honey: Antioxidant Activity, Inhibitory Effect on α-amylase and α-glucosidase, and In Vitro Digestibility Assessment

Abstract: In the present study, the effects of ultrasound (10, 20, and 30 min) on the bioactive compounds, antioxidant capacity, enzymatic inhibition, and in vitro digestion of six honey extracts from the Oaxaca state, Mexico, were analyzed. Significant differences were found in each honey extract with respect to the ultrasonic treatment applied (p < 0.05). In the honey extract P-A1 treated with 20 min of ultrasound, the phenols reached a maximum concentration of 29.91 ± 1.56 mg EQ/100 g, and the flavonoids of 1.92 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Recent studies have shown that oxidative stress is involved in the development and progression of various diseases such as cardiovascular diseases, tumors, and inflammation, and is one of the pathogenic mechanisms of such diseases [ 22 , 23 , 24 ]. Free radicals induce oxidative stress, and antioxidants can scavenge excessive free radicals produced in the body, due to which they have been a hot topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that oxidative stress is involved in the development and progression of various diseases such as cardiovascular diseases, tumors, and inflammation, and is one of the pathogenic mechanisms of such diseases [ 22 , 23 , 24 ]. Free radicals induce oxidative stress, and antioxidants can scavenge excessive free radicals produced in the body, due to which they have been a hot topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 10 min was chosen as the optimal extraction time for extraction of honey polyphenols because a shorter extraction time can save time and costs. In the study by Peláez-Acero et al [35], significant differences were found in extracts of six Mexican honey samples with respect to the ultrasonic treatment applied (10, 20, and 30 min), and the polyphenols reached a maximum concentration with 20 min of ultrasound. According to Borrás-Enríquez et al [36], an increase in the concentration of polyphenolic compounds from mango manilla residues was observed between 10 and 20 min, while a decrease in concentration was observed for a period longer than 20 min.…”
Section: Uae Optimizationmentioning
confidence: 92%
“…A mass of honey sample (1 ± 0.001 g) was mixed with 25 mL of aqueous ethanol solution (70%, v/v) and stirred in a magnetic stirrer for 15 min. Then, extraction was carried out in an ultrasonic bath (Elmasonic P, Elma Schmidbauer GmbH and Co., Singen, Germany) varying sonication time (10, 20, 30 min), temperature (35,50, 65 • C), and ultrasound amplitude (30, 60, 90%). The extracts were filtered (no.…”
Section: Uaementioning
confidence: 99%
See 2 more Smart Citations